Ulnar Goniometer Device: Comparison between electro-neurography and ultrasound. - Lara Gallicchio; Valentina Recchia; Pietro Guida; Anna De Luca; Luigi Didonna; Marianna Cipriani Cipriani; Eleonora Vecchio; Laura Ruiz Marquez; Antonella Petruzzellis; Filippo Tamma (Università degli Studi di Torino, 2024)
OBJECTIVE Our study aims to extend the previous research and compare two diagnostic methods performed on the ulnar nerve to validate the use of the ulnar goniometer in electromyographic diagnostic practice. Comparing the electroneurographic method, obtained through conduction velocity (CV) studies with ultrasound of the ulnar nerve in the area above the elbow and at the wrist, we aim to quantify the reliability of the ulnar goniometer compared to the diagnostic method ultrasound of the nerve. MATERIALS AND METHODS The operator examined with the use of the Ulnar Goniometer, detecting the wrist-below-elbow motor conduction speed and the above-elbow speed (AE), below-elbow speed (BE) and subsequently performed an ultrasound examination of the ulnar nerve in the forearm and elbow. We calculated the degree of homogeneity between measurements. RESULTS Evaluating 30 participants of both genders with typical paresthetic symptoms of ulnar nerve compression at the elbow, 100% of the measurements show that a decrease in Motor Conduction Velocity (MCV) below 50 m/s is associated with an increase in Cross-Sectional Area (CSA). Additionally, in 89% of cases, a reduction in MCV wBE and BEAE by more than 10 m/s is correlated with an increase in CSA. DISCUSSION AND CONCLUSIONS The measurement of the angle below the elbow (BE) and above the elbow (AE) using the Ulnar Goniometer provides us with a slowed Motor Conduction Velocity (MCV) that is by ultrasound data showing an increase in the Cross-Sectional Area (CSA) of the ulnar nerve in that segment, as observed in Cubital Tunnel Syndrome (CTS).